Cultivating rural healthcare professionals: the Norfolk General Hospital Health Science Perspectives Program. - Vancso L; Foster R; Moses EL (Hospital Quarterly)
Studies around the world have shown that where healthcare professionals establish their practices is influenced by where they grow up and receive their training. In our Simcoe, Ontario-based Norfolk General Hospital (NGH), about 40% of our physicians and 80% of other medical health professionals study nearby and return here to their rural roots.